Factors associated with Mortality outcome of intubated elderly In Hospital USM - Abdullah, Nurul Huda (2020)
Background: Since for the past few years till now, we are facing the increasing size of elderly group because of reduced mortality rate but with high birth rate. This ageing population may result in increasing requirement for health care facilities including critical care unit for the elderly. This study was aimed at identifies the factors which associated with mortality outcome of intubated elderly patients’ in hospital. Method: Retrospective cross sectional study of intubated elderly aged 60 years old and above which admitted to ICU/ High dependency ward (HDW) Hospital USM from 1st November 2019 till 30th May 2020 for 6 months. Data were collected using hospital computer base data and medical record. Factors were identified including demographic profile, comorbids, indication of intubation, diagnosis upon admission, organ dysfunction, intervention received, ventilation duration and complication with length of hospital stay to compare with 30 days mortality outcome. Result: Of the 155 intubated elderly patient, only 115 patients were eligible for this study after excluding few criteria with mean (SD) age 68.84 ±7.310(60-93). From this study, the factors independently associated with 30 days mortality in chi square test were respiratory distress as the indication of intubation (χ²(1)= 3.869, p 0.049) , patient was diagnosed with acute stroke upon intubation (χ²(1)=6.003, p 0.014), had organ dysfunction intermediate and low severity SAPS II score (χ²(1)=5.365, p 0.021; χ²(1)=12.114, p 0.001), coagulopathy (χ²(1)=5.546, p 0.019), hyponatremia (χ²(1)=6.385, p 0.012), hypoalbuminemia (χ²(1)=5.052, p 0.025), elevated transaminases (χ²(1)=7.591, p 0.006), patient on vasopressor usage (χ²(1)=18.321, p <0.001), ventilated less than 48 hours (χ²(1)=9.529, p 0.002) and underwent tracheostomy (χ²(1)=10.092, p 0.001), In multiple logistic regression, factors independently associated with low risk of mortality were low severity SAPS II score (odd ratio [OR] 0.149 confidence interval [CI] 0.047, 0.476) and underwent tracheostomy (OR 0.053 CI 0.010,0.284) while factors associated with high risk of mortality were patient with elevated transaminases (OR 3.373 CI 1.133,10.040, vasopressor usage (OR 21.183 CI 3.867,116.045), and ventilation duration less than 48 hours (OR 5.610 CI 1.351,23.303) . Conclusion: 30 days mortality outcome among intubated elderly patient depends not on the premorbid or age but based on the clinical presentation and biochemical abnormalities which indicated the severity of the illness and management in the intensive care unit